PD-L1 expression is an independent predictor of favorable outcome in patients with localized esophageal adenocarcinoma - Kollmann, Dagmar; Ignatova, Desislava; Jedamzik, Julia; Chang, Yun-Tsan; Jomrich, Gerd; Baierl, Andreas; Kazakov, Dmitry; Michal, Michal; French, Lars E; Hoetzenecker, Wolfram; Schatton, Tobias; Asari, Reza; et al. (Oncoimmunology, 2018)
Background. The outcome of patients with adenocarcinoma of the esophagogastric junction (AEG) remains poor. The programmed cell-death-protein-1 (PD-1), a co-inhibitory receptor primarily expressed by T-cells, represents a potential new therapeutic target. PD-1, PD-1 ligand 1 (PD-L1), and PD-L2 expression have all been described as prognostic factors in a variety of cancers. Their expression patterns in AEG, however, are poorly understood. We analyzed PD-L1, PD-L2 and PD-1 expression by tumor-infiltrating lymphocytes (TILs) and cancer-cells in tumor-biospecimens in AEG-patients. Methods. 168 patients who underwent esophagectomy because of AEG between 1992-2011 were included in this study. PD-L1, PD-L2 and PD-1 expression were evaluated by immunohistochemistry and correlated with various clinicopathological parameters, disease-free survival (DFS) and long-term overall survival (OS). Results. PD-L1 expression by cancer-cells (cancer-cell-PD-L1+) was found in 43.5% of patients whereas PD-L1 expression by TILs (TILs-PD-L1+) was observed in 69%. PD-L2 expression by cancer-cells and TILs was only found in 3.5% and 1.8%, respectively. Additionally, 77.4% of tumors contained PD-1+-cancer-cells and 81% PD-1+-TILs. Patients with increased expression of PD-1 by cancer-cells and TILs showed significantly reduced OS and DFS, as determined by univariate, but not multivariate analysis. Expression of PD-L1 by cancer-cells was found to be an independent predictor for improved DFS (p = 0.038) and OS (p = 0.042) in multivariate analysis. Conclusions. Cancer cells and TILs displayed PD-L1 expression in around 50% and PD-1 expression in around 80% of tumor-biospecimens obtained from AEG patients. Expression of PD-L1 is an independent predictor of favorable outcome in AEG, whereas PD-1 expression is associated with worse outcome and advanced tumor stage.
Keywords: esophageal adenocarcinoma; PD-L1; esophageal carcinoma; PD-L2; PD-1